2001
DOI: 10.1128/jcm.39.10.3446-3451.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Specific Method for Rapid Identification of Streptococcus pneumoniae Using Real-Time Fluorescence PCR

Abstract: Molecular surveillance of pathogens has shown the need for rapid and dependable methods for the identification of organisms of clinical and epidemiological importance. As the leading cause of community-acquired pneumonia, Streptococcus pneumoniae was used as a model organism to develop and refine a real-time fluorescence PCR assay and enhanced DNA purification method. Seventy clinical isolates of S. pneumoniae, verified by latex agglutination, were screened against 26 negative control clinical isolates employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 41 publications
5
122
1
2
Order By: Relevance
“…In a recent comparative study, Messmer et al reported that PCR amplification of an internal fragment of lytA was the most appropriate approach to the correct identification of S. pneumoniae (26). A similar conclusion had been reached in previous studies (17,25).…”
supporting
confidence: 63%
“…In a recent comparative study, Messmer et al reported that PCR amplification of an internal fragment of lytA was the most appropriate approach to the correct identification of S. pneumoniae (26). A similar conclusion had been reached in previous studies (17,25).…”
supporting
confidence: 63%
“…A TaqMan probe specific to the lytA gene was used to identify cultured S. pneumoniae by real-time PCR (McAvin et al, 2001). Using purified bacterial genomic DNA, the PCR assay was found to be both sensitive and specific, but was not tested on clinical specimens.…”
Section: Resultsmentioning
confidence: 99%
“…All of these tests are based on the use of Statens Serum Institute Omni serum, a reagent that contains capsular antibodies to all known serotypes of S. pneumoniae. Conflicting reports of sensitivity and specificity exist (6,7,8,12,35,37,40,53,56,63). One of the limitations of the agglutination test kits, as with other immunologic techniques, is that pneumococcal cells without capsules may not react, resulting in false-negative results.…”
mentioning
confidence: 99%